Promoting students’ interest and achievement in mathematics through “King and Queen of Mathematics” initiative - Kihwele, Jimmy E; Mkomwa, Jamila (Journal of Research in Innovative Teaching & Learning, 2024)
A reseach article submitted to the Journal of Research in Innovative Teaching & Learning. Vol. 16 of 2022.